Structure and agency in entrepreneurship research - An alternative research framework - Jayasinghe, Kelum N. (My University, 2003)
This paper critically examines the traditional and contemporary approaches towards conducting entrepreneurship research and emphasises the need for alternative research frameworks for future entrepreneurship research. The paper considers the implications of using different social theories to understand entrepreneurial issues at the rural community level. It particularly discusses on how to adopt ‘Structuration theory’ (Giddens, 1979, 1984) as an alternative framework for future entrepreneurship research. This proposed framework openly supports humanistic approaches to researching such entrepreneurial issues and in the clear recognition of the existence of multiple realities. It argues that proposed framework would expand the pluralist world of entrepreneurship research and particularly capable to see insights of ‘power related issues’ in establishing rural micro entrepreneurship, which is understandably difficult to research in positivist standpoint. The paper finally demands future entrepreneurship researchers to be more innovative and adopt alternative research frameworks within multiple reality ontology, instead of concentrating only the traditional positivist tradition of research within single ontology orientation.